2019
DOI: 10.2478/acve-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

NTS Targeted By miR-182 Modulates the Apoptosis of Goat Endometrial Epithelial Cells

Abstract: Neurotensin is a tridecapeptide that functions in prenatal metabolism. It is targeted and downregulated by miR-182 through binding the seed site of miR-182 to the 3′ untranslated region and reduced by a candidate tumor suppressor, testin. Considering that apoptosis is critical in the development of mammalian preattachment embryos, this study investigated the modulation of neurotensin to the apoptosis of goat endometrial epithelial cells and apoptosis-related proteins (P38 MAPK and caspase8). Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Recently, researchers found that miRNAs can bind to 3’ untranslated region (3’ UTR) of target messenger RNAs (mRNAs) and negatively regulate gene expression by transcriptional or translational inhibition [ 1 , 2 , 3 ]. MiR-574-5p are implicated in the pathophysiology of many tumors, including breast cancer, colorectal cancer and other oncoma [ 4 , 5 , 6 ]. In addition, miR-574-5p is a very important regulator for cell migration and proliferation [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers found that miRNAs can bind to 3’ untranslated region (3’ UTR) of target messenger RNAs (mRNAs) and negatively regulate gene expression by transcriptional or translational inhibition [ 1 , 2 , 3 ]. MiR-574-5p are implicated in the pathophysiology of many tumors, including breast cancer, colorectal cancer and other oncoma [ 4 , 5 , 6 ]. In addition, miR-574-5p is a very important regulator for cell migration and proliferation [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%